Gulf War and health. (National Academies Press, 2008)
The focus of this report, by the Institute of Medicine (IOM) Committee on Gulf War and Health: Physiologic, Psychologic, and Psychosocial Effects of Deployment-Related Stress, is the long-term effects of deployment-related stress. What happens to military personnel when they are subjected to the many stressors that occur in a war zone?